KOMPOSISI HASIL TANGKAPAN DAN TINGKAT KELAYAKAN USAHA RUMPON PORTABLE DAN RUMPON TRADISIONAL MENGGUNAKAN PANCING ULUR DI PERAIRAN ACEH BARAT - Syarifah Zuraida; Jaliadi Jaliadi (Universitas Teuku Umar, 2018)
FAD in the beginning when fishermen see hordes of pelagic fish congregate naturally around the objects floating on the surface. The level of eligibility criteria is top venture capital investment or long term investment in a particular production. The analysis needs to be done in order to know the development of the business at any given time. Field research conducted in July-August 2016, housed in the waters of West Aceh Meulaboh. Data retrieval is performed using the method of experimental fishing and survey (interview). Data were analyzed with the catch using a descriptive approach. The catch is that caught on portable FAD by using fishing line output with total as many as 622 tail and on traditional FAD as much as 1.171 tail for 30 trip. Portable FAD catches of 34.37% and traditional FAD of 65.63%. The investment required in portable FAD amounting to Rp 51.000.000. Total fixed costs incurred per annum on Rp 15.600.000 portable FAD and cost not fixed at RP 102.240,000. Tradisional FAD cost of Rp 53.000.000. Total fixed costs incurred per year amounting to 15.600.000 and cost is not a fixed amount of Rp 102.240,000. The results of calculations on venture portable FAD retrieved value NPV of Rp 20.137. 984, IRR of 36.86%, Net B/C of 1.39 and PP of 1.99 and on traditional FAD NPV values obtained amounting to 43.773.096, IRR of 60.30%, Net B/C of 1.83, PP amounting to 1.38. Financial analysis using bank rates of 14% by the year 2016. Keywords: Portable FAD, traditional FAD, West Aceh Waters